Narrative methods for the human sciences - Riessman, Catherine Kohler (Los Angeles : Sage Publications, 2008)
"Catherine Kohler Riessman provides a lively overview of qualitative research based on interpreting stories. Designed to improve research practice, it provides detailed discussions of four analytic methods: thematic analysis, structural analysis, dialogic/performance analysis, and visual narrative analysis." "Broad in scope, Narrative Methods for the Human Sciences offers concrete guidance for students and established scholars wanting to join the "narrative turn" in social research."--BOOK JACKET.
Looking back, looking forward -- Constructing narratives for research -- Thematic analysis -- Structural analysis -- Dialogic performance analysis -- Visual analysis -- Truths and cautions.
Includes bibliographical references (p. 225-244) and index.
Keywords: Narrative inquiry (Research method)